Influence of housing type on the cecal environment of horses. Issue 2 (24th April 2019) - Wolford, Ashley N; Coverdale, Josie A; Leatherwood, Jessica L; Pinchak, William E; Anderson, Robin C; Wickersham, Tryon A
Abstract: Eight previously cecally cannulated Quarter Horse geldings were utilized in a crossover design with two 28-d periods with a 21-d washout period between to evaluate the influence of housing on the cecal environment and dry matter intake (DMI). Horses were adapted to diet and housing from day 1 to 19, DMI was determined from day 20 to 24, and cecal fluid was collected on day 28. Horses were paired by age and body weight (BW) and randomly assigned to treatment. Treatments consisted of housing horses individually in stalls or group housed in a pen. Regardless of treatment, all horses were individually fed a pelleted concentrate at 1% BW (as fed) offered twice daily 12 h apart. All horses had ad libitum access to coastal bermudagrass hay ( Cynodon dactylon ). Hay was offered to stalled horses initially at 2% BW (as fed) and then adjusted based on 120% of a previous 3-d average of voluntary intake. A dual marker system was used to estimate forage consumption in all horses, using titanium dioxide (TiO2 ) as the external marker and acid detergent insoluble ash (ADIA) as the internal marker. TiO2 was offered at 10 g/d for 10 d with fecal samples collected on the final 4 d at 12-h intervals advancing by 3 h each day to account for diurnal variation. Cecal samples were collected on day 28, 4 h after the morning meal and immediately analyzed for pH, total anaerobic and lactic acid bacteria populations, methane and ammonia concentrations, as well as volatile fatty acid (VFA) concentrations. Data were analyzed using the PROC GLM procedure of SAS with the model containing effects for horse, period, and treatment. Cecal pH was affected by housing ( P = 0.02) with group-housed horses having lower cecal pH values compared with stalled horses (6.52 vs. 6.69, respectively). There was no influence of housing on populations of total anaerobic or lactic acid bacteria. Furthermore, housing did not influence cecal concentrations of VFA or methane and ammonia concentrations. Estimates of voluntary forage DMI were greater for group-housed horses ( P = 0.04) than stalled (8.47 and 5.17 ± 0.89 kg DM/d, respectively). In conclusion, confinement housing did not, with the exception of pH, alter cecal environment of a horse when similar diets were offered but did affect forage consumption.